2008
DOI: 10.1111/j.1600-0587.2008.05564.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical distribution and regional dynamics of twoBrassicaspecies

Abstract: Plants often show a patchy distribution. This can be related to the discontinuous distribution of environmental variables that define suitable habitat. Metapopulation theory suggests that additional patchiness may be caused by the dynamics of local extinctions and recolonisations. However, the contribution of these two mechanisms to explaining the observed patterns, and thus the applicability of metapopulation theory to plants remains controversial partly because population turnover may occur at long time-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 72 publications
1
33
0
Order By: Relevance
“…These wild cabbage populations generally are regarded as the native wild form of cultivated cabbage (Wichmann et al 2008). The three wild populations were located at sites known as ‘Old Harry’ (‘OH’, 50°38′N, 1°55′E), ‘Kimmeridge’ (‘KIM’, 50°35′N, 2°03′E), and ‘Winspit’ (‘WIN’, 50°36′N, 2°07′E).…”
Section: Methodsmentioning
confidence: 99%
“…These wild cabbage populations generally are regarded as the native wild form of cultivated cabbage (Wichmann et al 2008). The three wild populations were located at sites known as ‘Old Harry’ (‘OH’, 50°38′N, 1°55′E), ‘Kimmeridge’ (‘KIM’, 50°35′N, 2°03′E), and ‘Winspit’ (‘WIN’, 50°36′N, 2°07′E).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, recent studies have shown that the upregulation of genes in the aliphatic biosynthetic pathway causes a reciprocal repression in the indole pathway, and vice versa (Reviewed in Gigolashvili et al, 2009). Natural populations of B. oleracea tend to be very long-lived (Wichmann et al, 2008) and show inter-and intra-population variation in aliphatic glucosinolates (Mithen et al, 1995b;Moyes et al, 2000), providing sufficient variation in this aspect of antiherbivore chemistry to allow powerful experiments and surveys. Furthermore, Newton et al (2009) found that variation in herbivore attack on B. oleracea plants and populations were linked strongly to presence/absence patterns of aliphatic glucosinolates.…”
Section: Study Systemmentioning
confidence: 97%
“…Brassica nigra (L.) W.D.J Koch is an annual, predominantly outcrossing species that occurs in disturbed coastal and river valley habitats, such as coastal wetlands, cliffs and marshes, river banks, arable fields and ditch edges (Klotz et al 2002;Watson-Jones et al 2006, Wichmann et al 2008. It has been introduced to central and western Europe as a crop plant for oil and mustard production, but information on its origin and date of introduction varies widely in the literature; some floras even consider the species to be native (Klotz et al 2002;Preston et al 2002).…”
Section: Study Species Populations and Samplingmentioning
confidence: 99%